PENGARUH DISIPLIN KERJA, TURNOVER INTENTION DAN MOTIVASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT.GIGA PUTRA PERKASA KABUN - Gultom, Wahyu Exaudi; Setianingsih, Rahayu; Binangkit, Intan Diane (Jurnal Daya Saing, 2024)
This research aims to examine the influence of work discipline, turnover intention and motivation on the work productivity of PT Giga Putra Perkasa Kabun employees. the research method is quantitative with primary data obtained from questionnaires. the sample for this research is 100 employees. the data analysis technique is multiple linear regression analysis. then the sample was tested using the SPSS version 25 program. based on the results of linear regression analysis with a significance level of 5%, the results of this study concluded: work discipline has a positive and significant effect on employee work productivity, turnover intention has a negative and significant effect on employee work productivity and motivation has a positive and significant effect on productivity performance of PT Giga Putra Perkasa Kabun Employees. Keywords: Work Discipline, turnover intention, Motivation and Work Productivity